P-340 The endometrial switch following progesterone exposure correlates with uterine peristalsis. (30th June 2022) - Moliner, B; Fuentes, A; Gavilan, C; Alcaraz, B; Herencia, A; Bernabeu, A; Bernabeu, R
Abstract: Study question: What is the effect of the changes of the endometrium following progesterone exposure on uterine peristalsis? Summary answer: Uteri with a greater increase endometrial thickness after progesterone exposure have significantly greater uterine peristalsis (UP). Therefore, endometrial compaction is associated with quieter uteri. What is known already: Endometrial compaction is considered a sign of adequate response to progesterone. However, it is not always possible to visualize it. Little is known about endometrial switch following progesterone and its consequences after frozen embryo transfer, although it is hypothesized that increased endometrial growth after the window of implantation may be related to an increase in endogenous or exogenous oestrogen causing impairment of progesterone function. On the other hand, the role of progesterone in inhibiting endometrial contractile function is well known. Consequently, both the change in endometrial thickness and uterine contractility are indicators of progesterone function. Study design, size, duration: This retrospective observational was carried out in Instituto Bernabeu of Alicante. The study included 215 patients with at least three previous implantation failures after egg donation treatment, which underwent uterine peristalsis assessment the day of embryo transfer from June 2017 to December 2021. Participants/materials, setting, methods: UP assessment was performed using 4D ultrasound, recording a video for 6 minutes. UP variable was split in quartiles, and then the last quartile (UP ≥ 1, 5 contractions per minute) was considered the hypercontractility group. All patients had performed an ultrasound to assess endometrial thickness between 7 to 10 days before embryo transfer. Endometrial compaction has been considered when it has decreased. Endometrial switch (ES) is considered the percentage between both endometrial measures. Main results and the role of chance: The mean age of patients was 40, 11 years who underwent an average of 3, 75 embryo transfers. The average UP was 1, 09 contractions per minute. The average ES was 9% of increased endometrium. Only 83 (38, 6%) patients had endometrial compaction. To assess the association between UP and endometrial switch after progesterone exposure a univariate assessment was performed using Pearson's correlation resulting in a negative correlation (r=-0, 16; p = 0, 019). It was used the hypercontractility group for performing bivariate logistic regression was performed to examine the effect of independent variables (previous miscarriages, previous pregnancies, C-section, endometriosis, adenomyosis, myomatosis and endometrial preparation) on ES. Greater ES is statistically associated to greater UP with OR 1, 013 (95%IC: 1, 002 to 1, 025; p = 0, 041). Limitations, reasons for caution: It is a retrospective study based in patients with multiple implantation failure. It is possible that our conclusions couldn't be the same in patients with good prognosis. Wider implications of the findings: Assessment of endometrial changes and uterine peristalsis provide information about the response of the uterus to progesterone exposure. However, more studies assessing it prospectively both would be interesting to define which population has high risk to develop situations with inadequate progesterone response. Trial registration number: Not applicable